Periodontitis and risk of prevalent and incident coronary heart disease events. (9th November 2020) - Winning, Lewis; Patterson, Christopher C.; Linden, Katie; Evans, Alun; Yarnel, John; McKeown, Pascal P.; Kee, Frank; Linden, Gerard J.
Abstract: Objective: To investigate periodontitis as a risk factor for prevalent and incident coronary heart disease (CHD) in a group of middle‐aged men from Northern Ireland. Methods: A representative sample of 1400 dentate men had a comprehensive periodontal examination between 2001 and 2003. Prevalent and incident CHD events were validated by independent cardiologists. Logistic regression was used to assess the cross‐sectional relationship between periodontitis and prevalent CHD and Cox's proportional hazards analysis to assess the longitudinal relationship between periodontitis and incident CHD. Results: The mean age of the men at baseline was 63.7 (SD 3.0) years. Of the 1400 men examined, 126 (9%) had prevalent CHD. After adjusting for confounding variables, men with highest mean CAL (Q4) had an odds ratio of 2.15 (95% CI 1.15–4.02), p  = 0.02 for prevalent CHD in comparison to men with the lowest CAL (Q1). During a median follow‐up of 12.7 years, 137 (10.8%) of the 1274 men free of CHD at baseline had an incident CHD event. After adjusting for confounding variables, the hazard ratio for incident CHD in men in Q4 versus Q1 CAL categories was 1.36 (95% CI 0.81–2.29), p  = 0.24. Conclusions: In this group of dentate men, periodontitis was associated with prevalent CHD. However, there was no association with incident CHD.